2019
DOI: 10.1038/s41598-019-54191-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comorbidity Burden on The Association between Vascular Access Type and Clinical Outcomes among Elderly Patients Undergoing Hemodialysis

Abstract: The optimal vascular access type for elderly hemodialysis patients is controversial. We evaluated the impact of comorbidity burden on the association between vascular access type and mortality risk among 23,100 hemodialysis patients aged ≥65 years from the Korean Society of Nephrology End-Stage Renal Disease registry data. Subjects were stratified into tertiles according to the simplified Charlson comorbidity index (sCCI), and the survival and hospitalization rates were compared with respect to vascular access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
2
14
0
2
Order By: Relevance
“…25,26 To balance these two outcomes, it is important to implement better methods to maintain AVF to support more frequent hemodialysis. Consistent with our findings, CCI has been reported to be a risk factor for thrombosis and/or stenosis, 27,28 which causes VA failure and is related to increased mortality and hospitalization of hemodialysis patients. 29 Therefore, nurses should pay attention to the assessment of CCI to provide targeted protective measures for the patient's AVF care to reduce the incidence of thrombosis and stenosis.…”
Section: Discussionsupporting
confidence: 91%
“…25,26 To balance these two outcomes, it is important to implement better methods to maintain AVF to support more frequent hemodialysis. Consistent with our findings, CCI has been reported to be a risk factor for thrombosis and/or stenosis, 27,28 which causes VA failure and is related to increased mortality and hospitalization of hemodialysis patients. 29 Therefore, nurses should pay attention to the assessment of CCI to provide targeted protective measures for the patient's AVF care to reduce the incidence of thrombosis and stenosis.…”
Section: Discussionsupporting
confidence: 91%
“…31,32 The use of vascular graft worsens patient prognosis; in this sense, Jhee et al reported that the use of vascular graft showed a higher risk of all-cause mortality than AVF in patients with higher comorbidity (HR 1.3; CI of 95% 1.02-1.75, p = 0.004). 33 The AVFs are used less frequently among elderly patients than among younger patients. 34 Robinson et al showed that almost a quarter of older adults with incident ESKD and a central venous catheter as primary access were not referred for AV access placement due to medical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for HD catheter dysfunction at 1 year was estimated at 15% [28]. Hospitalization rates due to access malfunction were higher among patients with tunneled catheters than among those with fistulas [29,30]. Dysfunction of a tunneled catheter can be due to thrombosis, fibrin sheath formation, stenosis, kinking, or malposition of the catheter [19].…”
Section: Discussionmentioning
confidence: 99%